Bi‐directional organic light‐emitting diodes with nanoparticle‐enhanced light outcoupling. Issue 6 (8th October 2013) - Chang, Hong‐Wei; Lee, Jonghee; Koh, Tae‐Wook; Hofmann, Simone; Lüssem, Björn; Yoo, Seunghyup; Wu, Chung‐Chih; Leo, Karl; Gather, Malte C.
<x xml:space="preserve">Abstract</x> An effective method is presented for enhancing the outcoupling efficiency of translucent/bi‐directional organic light‐emitting diodes (TL/BD‐OLEDs) with a bottom indium tin oxide (ITO) anode and a top cathode comprised of a thin Ag layer covered with an organic capping layer. Upon insertion of a nanoparticle (NP)‐based scattering layer (NPSL) between the substrate and the ITO anode, the TL/BD‐OLEDs exhibit significantly enhanced external quantum efficiency (EQE) in both emission directions. Furthermore, the NPSL improves the color stability of the TL/BD‐OLEDs over a wide range of viewing angles. Simulations based on geometrical and statistical optics are performed to elucidate the mechanism by which the efficiency is enhanced and to establish strategies for further optimization. Simulations performed on the scattering layers with varying NP volume percentage reveal that the bottom‐side emission is governed by competition between waveguide‐mode extraction and backward scattering by NPs in the film, while the top‐side emission is largely dominated by the latter. Optimized bi‐directional OLEDs achieve a 1.64‐fold enhanced EQE compared to reference devices without NPSL. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>